‘Garden of Angels’ in the Past and Present – Historical and Contemporary Features of Kindergarten Education Students’ Metaphors of ‘Kindergarten’ (Training and Practice : Journal of Educational Sciences, 2018)
The aims of our research are to review the relations between the former and present concepts on the definition of ‘kindergarten’ and to explore the attributes of kindergarten teacher training students about the function and definition of ‘kindergarten’. We used a qualitative research methodology with document- and metaphor analyses with the participation of first-year students in Kindergarten Education BA training program. Our students' metaphors were also compared with the requirements of National Curriculum of ECEC. Several idealistic and ‘romantic’ features were found in the concepts; therefore, innovative and reflective training contents need to be worked out to decrease the risk of reality shock that students need to face with.